Implementation of Demonstration Methods in Early Children's Akhlak Education - Astuti, Retno; Katoningsih, Sri (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, 2021)
Moral education is very important to instill from an early age. Because at that age the child is easily given good stimulation and the child does not recognize many negative things. Cultivating good behavior since childhood determines the next moral development. AimThis study is to examine the literature, articles and documentation of research results that identify the implementation of demonstration methods in early childhood moral education. This research method uses literature review in the form of primary articles of approximately 20 articles consisting of 15 national journals with a period of the last 5 years and 5 international journals with a period of 7 years using certain keywords. Variabel independent demonstration method, and the dependent variable early childhood moral education. Articles are based on treatment, findings and conclusions. Results and discussion This study found that the demonstration method in early childhood moral education obtained varied results in terms of the duration of application, the individuals involved, and its effectiveness. The demonstration method is intended to provide positive stimulation, teach, exemplify, and instill the values of good behavior in the classroom, school environment, home environment, and the environment around the child. The demonstration method can be used as a method for early childhood moral education. Conclusion The demonstration method can be used by an educator or parent in moral education from an early age.